2024
DOI: 10.1126/science.adj9223
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic diversity of cellulose-degrading gut bacteria in industrialized humans

Sarah Moraïs,
Sarah Winkler,
Alvah Zorea
et al.

Abstract: Humans, like all mammals, depend on the gut microbiome for digestion of cellulose, the main component of plant fiber. However, evidence for cellulose fermentation in the human gut is scarce. We have identified ruminococcal species in the gut microbiota of human populations that assemble functional multienzymatic cellulosome structures capable of degrading plant cell wall polysaccharides. One of these species, which is strongly associated with humans, likely originated in the ruminant gut and was subsequently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 83 publications
0
0
0
Order By: Relevance
“…Based on modern hunter‐gatherer societies, daily dietary fibre intakes may have been in the order of 70–130 g, much higher than the current targets of around 20–40 g in industrialised societies (Tannock, 2024 ). A study targeted at cellulose‐degrading ruminococci revealed that they are more prevalent and abundant in humans in non‐industrialised societies, in agreement with their consumption of cellulose‐rich diets (Moraïs et al., 2024 , Table 1 ). Higher abundance of Treponema species has also been found in traditional societies, a genus known to harbour pathogenic species (for example T. pallidum , T. denticola ).…”
Section: The Gut Microbiota Fibre and Health In Different Populationsmentioning
confidence: 83%
“…Based on modern hunter‐gatherer societies, daily dietary fibre intakes may have been in the order of 70–130 g, much higher than the current targets of around 20–40 g in industrialised societies (Tannock, 2024 ). A study targeted at cellulose‐degrading ruminococci revealed that they are more prevalent and abundant in humans in non‐industrialised societies, in agreement with their consumption of cellulose‐rich diets (Moraïs et al., 2024 , Table 1 ). Higher abundance of Treponema species has also been found in traditional societies, a genus known to harbour pathogenic species (for example T. pallidum , T. denticola ).…”
Section: The Gut Microbiota Fibre and Health In Different Populationsmentioning
confidence: 83%
“…It is possible that the effect of fib-CNF on intestinal bacteria led to weight loss. Numerous studies and review articles discuss the degradation of cellulose and other dietary fibers by intestinal bacteria [24][25][26][27][28][29][30][31][32][33][34]. Although cellulose is a central component of plant fiber and is abundant in diets with plant-derived foods, humans, like other mammals, rely on gut microbiota to break down cellulose.…”
Section: Discussionmentioning
confidence: 99%